Holocene resource exploitation along the Nile: diet and subsistence strategies of Mesolithic and Neolithic societies at Khor Shambat 1, Sudan. (December 2021) - Dunne, Julie; Jórdeczka, Maciej; Chłodnicki, Marek; Hardy, Karen; Kubiak-Martens, Lucy; Hoyo, Magdalena Moskal-del; Osypińska, Marta; Portillo, Marta; Sobkowiak-Tabaka, Iwona; Delgado-Raack, Selina; Bobrowski, Przemysław; Breeze, Paul S.; et al.
Abstract: Abstract : The subsistence practices of Holocene communities living in the Nile Valley of Central Sudan are comparatively little known. Recent excavations at Khor Shambat, Sudan, have yielded well-defined Mesolithic and Neolithic stratigraphy. Here, for the first time, archaeozoological, palaeobotanical, phytolith and dental calculus studies are combined with lipid residue analysis of around 100 pottery fragments and comparative analysis of faunal remains and organic residues. This holistic approach provides valuable information on changes in adaptation strategies, from Mesolithic hunter-gatherers to Neolithic herders exploiting domesticates. A unique picture is revealed of the natural environment and human subsistence, demonstrating the potential wider value of combining multiple methods.